Desain Kurikulum dan Perencanaan Pengembangan Pendidikan Agama Kristen Menurut Pendekatan Kurikulum Bobbitt dan Charters dalam Pembentukan Iman Jemaat di HKBP Pearaja Tarutung - Elsyanti Gultom; Andar Gunawan Pasaribu (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This research aims to analyze curriculum design and planning for the development of Christian Religious Education at HKBP pearaja Tarutung using the Bobbitt and Charters curriculum approach. Through a qualitative approach and case studies, this research explores the application of curriculum theories in the church context, as well as the strategies used by churches to respond to religious education needs that are relevant to current developments and the social conditions of the congregation. Data was obtained through in-depth interviews, observation of religious education activities, and analysis of implemented curriculum documentation. The research results show that HKBP pearaja Tarutung implements a curriculum based on the needs of the congregation with an approach that prioritizes the active involvement of the congregation in the planning and implementation process. Apart from that, the church also focuses on developing educators with regular training and the use of technology to support the learning process. It is hoped that this research can contribute to the development of the Christian Religious Education curriculum in other churches and enrich the discourse on Christian religious education in a more contextual and relevant way.